2004
DOI: 10.1299/jsmec.47.1062
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on Quantitative Role of Trunk Muscles in Spinal Stabilization

Abstract: The human lumbar spine can support much larger compressive loads if it is applied along a follower load path that approximates the tangent to the curve of the lumbar spine compared with the vertical load path. In this study, a musculoskeletal finite element model of the simplified lumbar spine including idealized psoas major muscles in the frontal plane was developed and the quantitative role of psoas major muscles was investigated to generate the follower load by using stiffness methods when vertical loads ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…3). FL were predicted [6,9,10]. In addition, the corresponding displacements and rotations at all nodes, as well as the follower forces, the shear forces, and 4 DISCUSSION the joint moments acting on those nodes were estimated in order to validate that the FL could increase Several experimental studies have shown that the load-carrying capacity increases when an external the load-carrying capacity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). FL were predicted [6,9,10]. In addition, the corresponding displacements and rotations at all nodes, as well as the follower forces, the shear forces, and 4 DISCUSSION the joint moments acting on those nodes were estimated in order to validate that the FL could increase Several experimental studies have shown that the load-carrying capacity increases when an external the load-carrying capacity.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding when the resultant force of all loads applied on the spine is directed in accordance to its curvature [1, the FL, simplified lumbar spine models in the frontal plane with five or ten idealized muscles were solved 2], which is called a 'follower load' (FL). The FL path can also provide clinically feasible ranges of intra-to estimate the muscle forces generating the FL direction using either a stiffness analysis method [6] discal pressure and intersegmental rotation while or a differential equation method [2]. However, to…”
Section: Introductionmentioning
confidence: 99%